Predictors of death in Malaysian HIV-infected patients on anti-retroviral therapy - Lubis, R.; Bulgiba, A.; Kamarulzaman, A.; Hairi, N.N.; Dahlui, M.; Peramalah, D. (2013)
Objective: To determine the predictors of death in Malaysian HIV-infected patients undergoing antiretroviral therapy (ART). Methods: Data from 845 HIV-infected patients aged 20 years on ART in a large teaching hospital in Malaysia from 1989 to 2009 were analyzed using Kaplan Meier and Cox regression analyses. Results: 72.7 of the patients survived. Multivariate Cox regression showed that significant predictors of death were age 50 years (HR 1.76; 95 CI 1.18 2.64), secondary education (HR 3.57; 95 CI 1.12 11.37), tertiary education (HR 3.57; 95 CI 1.0911.70), being unemployed (HR 1.49; 95 CI 1.07 2.09), AIDS on initial presentation (HR 5.75; 95 CI 3.29 10.07), single-drug ART (HR 1.84; 95 CI 1.27, 2.66), double-drug ART (HR 1.63; 95 CI 1.19 2.25) and inability to achieve viral load 50 copies/ml (HR 10.22; 95 CI 7.26 14.37). Conclusion: Every effort needs to be made to ensure that all HIV patients have access to triple drug ART, to lower viral load to 50 copies/ml and to treat HIV patients before they progress to AIDS as these are significant modifiable predictors of death in Malaysian HIV patients.